Secondary immune response in a vaccinated population during a large measles epidemic. - Ozanne, G (1992)
The rates of secondary immune response (SIR) and secondary vaccine failure (SVF) during a measles epidemic (10,184 notifications) were evaluated. A patient with SIR was defined as a subject for whom all sera were immunoglobulin G (IgG) positive and IgM negative with a significant increase in complement fixation titer. A patient with SVF was defined as a vaccinated symptomatic subject showing a SIR. Sequential sera from 898 subjects were tested for measles antibody by enzyme-linked immunosorbent assay (IgG and IgM) and by complement fixation. Evidence of recent anti-measles virus specific immune response was found in 496 subjects (55.5%). The vaccination rate was estimated at 74.6% (99% confidence interval [CI], 67.9 to 80.7%). The number of exposed vaccinated subjects was estimated at 370 (74.6% of 496). The SIR rate was 4.03% (20 of 496) (99% CI, 2.1 to 6.9%) among subjects with immune response. These 20 subjects were 2 with measles (Centers for Disease Control's definition), 6 with measles with rash of unknown duration, 8 with presumed measles with either rash or fever, 3 asymptomatic subjects (2 with recent contact with a measles case), and 1 undocumented subject. Since 3 patients with SIR were asymptomatic and 2 others were documented as not vaccinated, there was a maximum of 15 probable occurrences of SVF among the 20 patients with SIR. The SVF rate among exposed vaccinated subjects was estimated at 4.05% (15 of 370) (99% CI, 1.9 to 7.5%). In conclusion, neither prior vaccination nor detectable SIR ensures protective immunity. Measles virus may induce asymptomatic SIR in IgG-seropositive subjects. SVF led to typical or modified measles but did not seem to have played an important role during this epidemic.